Naming plants scientifically - CEV Multimedia ([United States] : CEV Multimedia, 2004)
The ability to recognize plants and learn their scientific names is an important part of most agricultural careers. In this Microsoft PowerPoint presentation, students learn the importance of using scientific names and are shown how to write them correctly. They will learn about Carolus Linnaeus and the system of binomial nomenclature. Terminology is given for successfully communicating plant information
Title from container
Registration codes : 397200-18092685-412961
System requirements: PC/MAC OSX, Office 2000 or better; IE 5.5; Internet connection; Adobe, Acrobat Reader, Flash 5 player
Keywords: Plants -- Nomenclature; Plant names, Popular